2016
DOI: 10.1021/acscatal.5b02920
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Atomic Level Surface Structure and Stability/Activity of Platinum Surface Atoms in Aqueous Environments

Abstract: The development of alternative energy systems for the clean production, storage, and conversion of energy is strongly dependent on our ability to understand, at atomic molecular levels, the functional links between the activity and stability of electrochemical interfaces. Whereas structure− activity relationships are rapidly evolving, the corresponding structure− stability relationships are still missing. This is primarily because there is no adequate experimental approach capable of monitoring the stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
272
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(288 citation statements)
references
References 66 publications
13
272
3
Order By: Relevance
“…For comparison, Jovanovic et al 18 reported 0.0045% or 150 μML for 3 nm Pt/C cycled between 0.05 V and 1.0 V at 5 mV/s and Lopes et al 19 reported 103±10 μML for 3 nm Pt/C cycled between 0.05 V and 1.05 V at 10 mV/s. The percentage reported here equates to a Pt dissolution rate of 3.8 × 10 −13 g-cm −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparison, Jovanovic et al 18 reported 0.0045% or 150 μML for 3 nm Pt/C cycled between 0.05 V and 1.0 V at 5 mV/s and Lopes et al 19 reported 103±10 μML for 3 nm Pt/C cycled between 0.05 V and 1.05 V at 10 mV/s. The percentage reported here equates to a Pt dissolution rate of 3.8 × 10 −13 g-cm −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…19 The silver electrode was made by coating a thin layer of micron-size silver particles on the glassy carbon working electrode of the BASi cell. The silver particles were firmly bound to the electrode using a thin film of perfluorosulfonic acid (PFSA) ionomer (5 wt% in lower aliphatic alcohols, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43][44][45][46][47][48] The transition metal cations evolved from the anode can reach the cathode even when an anion exchange membrane is utilized to separate the electrode chambers. 49 Whether this crossover occurs during operation or during the storage and cleaning of the electrochemical cell has yet to be resolved conclusively.…”
Section: Iii: Impact Of Impurities On Electrocatalytic Activitymentioning
confidence: 99%